PROYEKSI PENDUDUK INDONESIA 1990-2010 - Tukiran Tukiran (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1992)
The conformity betweenpopulation projection and both the survey and census results depends very much on the assumption used. The fertility, mortality, and the migration dynamics may affect both the number and structure of the projection results of the population. In line with this, the population projection is formed by using several different assumptions to be able to obtain a clear description about the minimum and maximum conditions of the population in the years to come.The population growth rate of Indonesia in the coming years is estimated to remain high as a consequence of the population structure of the younger age group. The fertility reduction that has taken place has only affected the number of population aged less than ten years, whereas the growth rate of the population aged ten years and over will remain high because of the mortility reduction. The main challenge of the future could be that the population number of the teenage group and the adolescence may be higher than that of the previous period. The female population of the productive age group and the population of the old age group have also increased in number. This phenomenon is very closely related with the expansion of the employment opportunities, consumtion needs, health services, and of many other facilities. The number of population of the economically productive age group and the eligible female age group will, in the coming years, be much greater than that in 1990. This needs serious and effective planning to tackle the problem so that it may not become a burdento the country's development.